STRATEGI PENINGKATAN KINERJA USAHA MELALUI PEMANFAATAN PLATFORM PEMASARAN DIGITAL TOKO VALENTA DI KECAMATAN TANAH ABANG - Agrina, Camelia Rizki; Kirana, Desty Hapsari (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Post-COVID-19 pandemic, digitalization has become one of the key strategies in enhancing the competitiveness of MSMEs, including Toko Valenta, a fashion business located in the Tanah Abang District. This research aims to analyze Toko Valenta’s digital marketing optimization strategy through social media platforms (Instagram, Facebook) and marketplaces (Shopee, Tokopedia) to improve its business performance. A qualitative descriptive method was employed, combining interviews, direct observation, and SWOT analysis. The research findings indicate that adopting digital marketing has the potential to increase brand visibility, market reach, and operational efficiency. However, Toko Valenta faces challenges such as the suboptimal utilization of digital media and intense competition in the fashion industry. Strategies focused on digital innovation, product quality improvement, and more personal interaction with customers are proposed to enhance competitiveness and business sustainability